2012
DOI: 10.1088/0029-5515/52/5/054003
|View full text |Cite
|
Sign up to set email alerts
|

Screening of resonant magnetic perturbations by flows in tokamaks

Abstract: The non-linear reduced four-field RMHD model in cylindrical geometry was extended to include plasma rotation, neoclassical poloidal viscosity and two fluid diamagnetic effects. Interaction of the static resonant magnetic perturbations (RMPs) with the rotating plasmas in tokamaks was studied. The self-consistent evolution of equilibrium electric field due to RMP penetration is taken into account in the model. It is demonstrated that in the pedestal region with steep pressure gradients, mean flows perpendicular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
160
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(169 citation statements)
references
References 39 publications
8
160
1
Order By: Relevance
“…and k i = −1 [12] are used. In the MAST case, the neoclassical friction is not included in the model.…”
Section: Physical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…and k i = −1 [12] are used. In the MAST case, the neoclassical friction is not included in the model.…”
Section: Physical Modelmentioning
confidence: 99%
“…Indeed, the total suppression of the type-I ELMs by RMPs was demonstrated in DIII-D [2,3] and later in ASDEX upgrade [4] and KSTAR [5]; the strong mitigation of the ELM size was also obtained in the JET [6], MAST [7] and NSTX [8] tokamaks, motivating the use of this method in ITER [2,9]. The non-linear MHD theory and modeling made significant progress to refine the understanding of the RMP interaction with the plasma [10][11][12][13][14][15]. In particular, it was demonstrated that the penetration of the RMPs in the plasma is conditioned by the rotating plasma response [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…(1) (l neo : neoclassical friction coefficient) is obtained from the radial force balance equation linking the radial electric field, pressure gradient, and poloidal velocity (detailed derivation can be found, for example, in Ref. 22). This term gives rise to mean E Â B flow generation due to pressure curvature.…”
Section: Simulation Modelmentioning
confidence: 99%